INCREASING THE CORROSION RESISTANCE OF HOT-ROLLED STEEL PIPES BY DYNAMIC DEFORMATION OF THE SURFACE COMBINED WITH INHIBITORY TREATMENT - Bohdan, Dmytro; Balakin, Valery; Kuznetsov, Evgeny; Nуkolayenko Yulia; Solovyova, Inna (SWorld-Ger Conference proceedings, 2023)
The results of experimental studies of the surface corrosion resistance and metallographic structure of 139x5 mm pipes made of steel grade 20 using three types of inhibitors and various modes of dynamic plastic deformation are presented.. It has been esta